Feasibility Analysis of Thermochemistry Senior High School Chemistry Textbook Based on Criteria of Four Steps Teaching Material Development Method - Sjaeful Anwar; Omay Sumarna; Andi Mulyadi (Postgraduate, University of Mataram, 2023)
This study was conducted to analysis properness of thermochemistry teaching material in chemistry school textbook which is used in most SMA/MA in Kota Bandung based on criteria of selection stage of Four Steps Teaching Material Development (4STMD) method. The type of research is evaluative research by content analysis method. There are three criteria in the selection process of 4STMD method. First is conformity with the curriculum, it is known that object of research is not yet fully in accordance with the demands of the Curriculum. In terms of material broadness, there are four concepts required by the curriculum that are not included in the teaching material, so that the teaching material is less broad. In addition, there are six concepts that are not required by the curriculum, but included in the material, so that the material is too broad. Thus, in general, the material broadness is not in accordance with the demands of the Curriculum. Meanwhile, in terms of concepts depth, from 31 concepts demanded by the curriculum, 18 concepts are less deep and three concepts are too deep. Based on second criteria, that is scientific correctness of the concepts, it is known that there are two concepts that are not scientifically correct according to references from international general chemistry textbooks and books published by IUPAC. Based on the third criterion, namely the cultivation of pedagogical context, it is known that the values and skill embedded in the material are religious values, creativity, curiosity, respect for achievement, responsibility, reading-interested, discipline, and environmental care